2022
DOI: 10.1186/s12995-022-00366-y
|View full text |Cite
|
Sign up to set email alerts
|

Occupational safety practice among metal workers in Bangladesh: a community-level study

Abstract: Background The overall information on occupational health and safety (OHS)-related knowledge and workplace practices are scarce in Bangladesh. This study aimed to (i) examine the prevalence of occupational injuries, (ii) explore the level of OHS-related knowledge and practice among workers and associated factors, and (iii) investigate the socioeconomic factors and OHS-related knowledge and practice scores as determinants of injury among metal workers at a community setting in Bangladesh. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Respondents said that there were 27.6% functioning hazard warnings and 40.2% of goods that were kept property [20] . Also, about workers awareness and knowledge Islam et al, (2022) [10] , 92.7% of respondents were aware of the health dangers connected to metal cutting sounds, and the majority of respondents (99%) were aware of the detrimental consequences of metal dust. To protect one's health at work, 99% of participants nearly unanimously agreed that one must wear shoes, masks, safety goggles, or glasses.…”
Section: Inspection Checklistmentioning
confidence: 96%
See 3 more Smart Citations
“…Respondents said that there were 27.6% functioning hazard warnings and 40.2% of goods that were kept property [20] . Also, about workers awareness and knowledge Islam et al, (2022) [10] , 92.7% of respondents were aware of the health dangers connected to metal cutting sounds, and the majority of respondents (99%) were aware of the detrimental consequences of metal dust. To protect one's health at work, 99% of participants nearly unanimously agreed that one must wear shoes, masks, safety goggles, or glasses.…”
Section: Inspection Checklistmentioning
confidence: 96%
“…The majority of them, 91.8%, 85.4%, and 61.3%, respectively, were wearing coveralls, goggles, and safety shoes [1] , this because of better awareness of workers by safety measures and importance of wearing PPE. Islam et al, (2022) [10] , Regarding PPE use, they found that 76.1% of the workers said they wore goggles, and 18.5% said they wore masks. At least 2.4% of those surveyed mentioned using safety shoes [10] .…”
Section: Ppe Usage and Safety Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of attention by managers, employee educational status, income, lack of training on health and safety, lack of knowledge on health and safety, negative/poor perception regarding health and safety measures, lack of procedures or regulations, lack of safety materials, and poor supervision/inspection are the main reasons for non-compliance with health and safety measures. [11][12][13] Small-scale industries in Ethiopia are among the most dangerous places to work, with an annual prevalence of selfreported occupational injuries ranging from 30% in the Bale Zone to 58.2% in Mekelle City. 14,15 Metal sectors have a greater rate of occupational injuries and majority of employees did not adhere to occupational safety and health standards such as proper use of personal protective equipment.…”
Section: Introductionmentioning
confidence: 99%